Edible Landscaping - Eva C. Worden; Sydney Park Brown (EDIS)
Revised! ENH-971, a 3-page fact sheet by Eva C. Worden and Sydney Park Brown, describes a landscaping practice that replaces plants that are strictly ornamental with plants that produce food. Published by the UF Department of Environmental Horticulture, November 2007.